Perbedaan Efektifitas Penggunaan Media Poster dan Metode Demonstrasi Terhadap Teknik Menyikat Gigi Pada Siswa - Saputro, Heri; Widiyastuti, Dini; Fazrin, Intan (STRADA : Jurnal Ilmiah Kesehatan, 2018)
The research design was comparation study by pre-test and pos-test approach for the two groups of treatment, by the population of all the first grade were 105 respondents devided into two groups, by the treatments of one group using poster treatment, and demonstration treatment for the other group, the sample is parts of the population were 96 respondents, by using random sampling. The data collection technique is using the observation sheets. The data was collected is proccesed by wilcoxon statistic test and mann-whitney U with significance ɑ = <0.05. The result of the research, half of the respondents, the technique of tooth brusing by using poster media is in the good category. That 24 respondents (50%), almost the respondents of tooth brushing as good was 35 respondents (72,9%), there is a defference in result of poster media group and demonstration method group